ANALYSIS OF PRODUCT DEMAND AND SUPPLY IN CONDITIONS OF MARKET INSTABILITY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article analyzes the situation when, due to inflation, market unevenness occurs, and market entities offer different prices for their goods and services. An algorithm has been developed to determine the coordinates of the supply and demand line based on data from marketing experts and the direction of the angular coefficient of the supply and demand line. Based on certain coordinates, a simplified scheme for calculating the equilibrium prices of products and a numerical example are given.